2021
DOI: 10.1101/2021.01.26.21250518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19 on education, health and lifestyle behaviour of Brazilian urology residents

Abstract: ObjectivesTo evaluate the impact of COVID-19 on clinical and surgical practice, educational activities, health and lifestyle behavior of Brazilian urology residents.Materials and MethodsA web-based survey was sent to 468 Brazilian urology residents from postgraduate years (PGY) 3 to 5 to collect data on clinical practice and training after 4 months of COVID-19. We also assessed health-related and behavior changes, rate of infection by SARS-CoV-2, deployment to the front line of COVID-19, residents’ concerns, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Several studies have demonstrated a decrease in non-COVID-related hospital admissions, including reductions in elective procedures (1)(2)(3)(4)(5). In Germany, non-COVID overall inpatient admissions decreased by 35% after the lockdown announcement, with even admissions for critical care conditions such as cancer treatment significantly reduced (4).…”
Section: Commentmentioning
confidence: 99%
“…Several studies have demonstrated a decrease in non-COVID-related hospital admissions, including reductions in elective procedures (1)(2)(3)(4)(5). In Germany, non-COVID overall inpatient admissions decreased by 35% after the lockdown announcement, with even admissions for critical care conditions such as cancer treatment significantly reduced (4).…”
Section: Commentmentioning
confidence: 99%
“…There should be initiatives towards health education for the general population concerning preventing Covid-19 and managing all other health care, especially in reducing collateral damage caused by delayed urgent diagnosis due to fear. This emergency public health crisis could be recognized as an opportunity to develop and better integrate telemedicine care such as telemonitoring as a standard in healthcare (33), as almost 40% of Brazilian urologists have experienced (34,35). It also may be a method to boost effi ciency and guide the prioritization of surgical lines (26).…”
Section: Discussionmentioning
confidence: 99%
“…Brezilya'da üroloji asistanlarında yapılan bir çalışmada pandemi sürecinde sigara ve alkol tüketiminde sırasıyla %53,6 ve %44,9 artış olduğu saptanmıştır 16 . Yalçın ve arkadaşları pandemi döneminde sağlık çalışanlarıyla yaptıkları çalışmada sigara içme %32,7, alkol kullanmanın %5,8 olduğu bildirilmiştir 17 .…”
Section: çAlışma Popülasyonu Ve Tasarımıunclassified